The Lost Circassia and the Found Circassians: Caucasian Migration to the Ottoman Empire - Veronika Tsibenko (Türkiyat Mecmuası)
The article deals with the history of pan-Caucasian (Circassian) nation-building in the context of international relations, which helps to provide a new look at the migration from the North Caucasus to the Ottoman Empire in the 19th century. The author analyses a wide range of materials including archival documents, historiographical works, and the British and French press to show that subjectification of the Caucasus in the international arena and Circassian nation-building were the real triggers of migration. The success of Western (primarily British) diplomacy can be seen in the formulation of the Circassian question and the emergence of a pan-Caucasian national project. However, Russia's military advancement in the Caucasus, and the difference between British and French foreign policy strategies halted the nation-building process. Besides, the efforts of nation-builders were not enough to unite North Caucasians, due to such obstacles as the lack of experience of common statehood, and linguistic and ethnic diversity. Thus, migration was the result of the failure of the British Circassian nation-building project, and it summed up the long period of subjectification of the North Caucasus in the international arena in the 19th century.